(untitled) (Indian Journal of Veterinary Pathology, 2025)
The present study was conducted to investigate hepatic damage associated with Dextran sodium sulphate (DSS) induced ulcerative colitis (UC) and to evaluate the ameliorative effect of Visnagin (VIS) against this hepatic damage. Six groups of C57BL/6 male mice, each containing six animals viz. Group 1 (Normal), Group 2 (DSS @ 2% with 3 cycles of 5 day intervals diluted in distilled water administered orally), Group 3 (VIS @ 60 mg/kg b.wt., orally), Group 4 (VIS @ 30 mg/kg b.wt. and DSS), Group 5 (VIS @ 60 mg/kg b.wt. and DSS) and Group 6 (Dexamethasone sodium @ 1 mg/kg b.wt. IP and DSS). After the 31-day experimental period, organ weights, serum analysis, oxidative stress parameters, inflammatory cytokines, gross and histopathology and immunohistochemical analysis were evaluated on day 32. Group 2 mice (DSS only) showed significant increase in ALT, AST, MDA and nitrite levels, along with elevated pro-inflammatory cytokines levels. Conversely, significant decreases in total protein, albumin levels, antioxidant enzymes levels (SOD, CAT and GSH) and IL-10 concentrations were observed. Histopathological examination revealed severe degenerative changes in the livers of Group 2, with increased NF-κB immunoexpression and reduced Nrf2 protein expression. Groups 4 and 5 treated with VIS, showed dose-dependent improvements with moderate to mild changes attributed to VIS’s anti-inflammatory and antioxidant properties likely through modulation of the Nrf2 signaling pathway. Group 6 treated with Dexamethasone, also showed improvement in all these parameters. In conclusion, VIS demonstrated notable anti-inflammatory and anti-oxidant properties against DSS-induced hepatotoxicity.